Guidelines for Scientific Writing - Valdivia, Omar Abreu; Morales, Netzahualcoyotl Velasco (Advances in Social Sciences Research Journal, 2022)
The article refers to an experience put into practice at the IPH University Institute of Mexico to improve the scientific writing of students of the different modalities. It was based on the study of the written texts produced by students of said institution, to determine the deficiencies that persist in their academic writing and develop a solution strategy on that basis. Methods, techniques and procedures were used, such as the documentary, historical, genetic, systemic, statistical, analysis and synthesis, hermeneutical, peer comparison methodology of expert criteria and as a study procedure, coding. of the works for its management in an analytical matrix. Its result consists of the elaboration and validation of a practical didactic alternative that serves as an instrument for the improvement of academic writing in this center.